The Effectiveness of The POE2WE Learning Model in Supporting Distance Learning in The Era of The Industrial Revolution 4.0 - Nana, Nana; Nugroho, Kuncoro Asih; Ahmad, Jamil (Jurnal Inovasi Pendidikan IPA, 2023)
In general, the competence of students who learn to dare is assessed to have decreased. The form of learning that can be used as a solution in the era of the industrial revolution 4.0 is distance learning. This research method is a quantitative descriptive study that aims to describe and analyze student responses regarding the application of the LMS-based POE2WE learning model. The research respondents were 233 students from two universities who came from the Physics Education study program, D4 Nursing and Professional Nurses in Tasikmalaya City. Data collection techniques used are questionnaires and observation. The questionnaire consisted of 15 positive statements related to the application of the LMS-based POE2WE learning model in supporting distance learning in the era of the industrial revolution 4.0. The results of the analysis obtained that from 233 students the average result was 4.01. This means that the average student agrees that the application of the LMS-based POE2WE Learning Model provides a good response and. This is an indication that the implementation of learning with the POE2WE model can be carried out in various learning backgrounds. The problems faced are related to increasing quotas and poor internal networks.